A highly stable and efficient carbon electrode-based perovskite solar cell achieved via interfacial growth of 2D PEA2PbI4 perovskite. Issue 47 (22nd November 2018) - Lee, Kisu; Kim, Jungwon; Yu, Haejun; Lee, Jong Woo; Yoon, Chang-Min; Kim, Seong Keun; Jang, Jyongsik
Abstract : Phenylethylammonium iodide (PEAI) treatment simultaneously improved the efficiency and stability of a carbon electrode-based perovskite solar cell. Abstract : Carbon electrode-based perovskite solar cells (PSCs) without hole transport materials (HTMs) are regarded as a promising alternative architecture to realize low-cost, stable photovoltaics. However, poor hole transport and severe charge recombination at the interface of perovskite and carbon layers degrade the power conversion efficiency (PCE) of carbon-based PSCs. Here we report on an innovative method to post-treat a carbon electrode with phenylethylammonium iodide (PEAI), for the growth of a two-dimensional (2D) perovskite at the interface between the perovskite and carbon layers. The resulting ultrathin PEA2 PbI4 layer formed within the perovskite/carbon interface improved the poor perovskite/carbon contact. The favorable conduction and valence energy levels of the 2D perovskite interlayer greatly suppressed interfacial charge recombination, which stems from the absence of an HTM. Using our fabrication method, the average PCE of devices was boosted from 11.5% to 14.5% with minimal hysteresis loss, and a maximum PCE of 15.6% was achieved. Moreover, the PEAI-treated devices showed excellent ambient stability. The dual protection of the hydrophobic carbon and 2D perovskite layers enabled the device to retain 92% of its initial PCE after 1000 h of exposure to ambient conditions (relative humidity: 40 ± 5%). The thermal stability of the devices was also enhanced, showing no efficiency loss after thermal testing at 150 °C, due to suppressed ion migration.